Effects of Ultra-Purified Alginate Gel Implantation on Meniscal Defects in Rabbits. Issue 3 (March 2019) - Kim, WooYoung; Onodera, Tomohiro; Kondo, Eiji; Kawaguchi, Yasuyuki; Terkawi, Mohamad Alaa; Baba, Rikiya; Hontani, Kazutoshi; Joutoku, Zenta; Matsubara, Shinji; Homan, Kentaro; Hishimura, Ryosuke; Iwasaki, Norimasa
Background: Many tissue-engineered methods for meniscal repair have been studied, but their utility remains unclear. Hypothesis: Implantation of low-endotoxin, ultra-purified alginate (UPAL) gel without cells could induce fibrocartilage regeneration on meniscal defects in rabbits. Study Design: Controlled laboratory study. Methods: Forty-two mature Japanese White rabbits were divided into 2 groups of 21 animals each. In each animal, a cylindrical defect measuring 2 mm in diameter was created with a biopsy punch on the anterior horn of the medial meniscus. In the control group, no treatment was applied on the left medial meniscal defect. In the UPAL gel group, the right medial meniscal defect was injected with the UPAL gel and gelated by a CaCl2 solution. Samples were evaluated at 3, 6, and 12 weeks postoperatively. For biomechanical evaluation, 6 additional samples from intact animals were used for comparison. Results: The macroscopic score was significantly greater in the UPAL gel group than in the control group at 3 weeks (mean ± SE: 5.6 ± 0.82 vs 3.4 ± 0.83, P = .010), 6 weeks (5.9 ± 0.72 vs 2.5 ± 0.75, P = .026), and 12 weeks (5.2 ± 1.21 vs 1.0 ± 0.63, P = .020). The histological score was significantly greater in the UPAL group than in the control group at 3 weeks (2.1 ± 0.31 vs 1.2 ± 0.25, P = .029) and 12 weeks (2.2 ± 0.55 vs 0.3 ± 0.21, P = .016). The mean stiffness of the reparative tissue in the UPAL gel group was significantly greater than that in the control group at 6 weeks (24.325 ± 3.920 N/mm vs 8.723 ± 1.190 N/mm, P = .006) and at 12 weeks (27.804 ± 6.169 N/mm vs not applicable [because of rupture]). Conclusion: The UPAL gel enhanced the spontaneous repair of fibrocartilage tissues in a cylindrical meniscal defect in rabbits. Clinical Relevance: These results imply that the acellular UPAL gel may improve the repair of traumatic meniscal injuries.